PERAN RSUD PAMBALAH BATUNG AMUNTAI DALAM IMPLEMENTASI PROGRAM BPJS KESEHATAN DI HULU SUNGAI UTARA - Jumaidi Jumaidi (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
The issues discussed in this study were the implementation of BPJS program on health in RSUD of Pambalah Batung, Amuntai. It is inspired by the complaints of patients who were admitted to redeem the drug, the number of beds and rooms which was not adequate as well as there were many facilities and infrastructures which were still in bad condition, and there were many people who were not aware of the availability of BPJS program on health. The samples of data sources used purposive sampling technique. As many as 10 people were considered to have strong relations with the issues examined. The data were collected by observations,interviews,and documentation. The survey results revealed: the constraint from the aspect of the unclear communication which resulted in the delays of service process carried out by the Executive of RSUD, the aspect of resources interms of facilities which was still in sufficient because there were many health facilities which were not functioning properly and in damaged condition.It is suggested to socialize BPJS on health program more often by RSUD of Pambalah Batung through flags, banners, and localtelevision, toad health facilities for BPJS patients especially in patient and sanitary rooms, to repair damaged facilities. The addition of internet (wifi), particularly for Emergency Room (ER) is required when information on JKN program is in need.